Toward Therapeutic Drug Monitoring of Lenalidomide in Hematological Malignancy? Results of an Observational Study of the Exposure-Safety Relationship - Song, Zaiwei; Ma, Lan; Bao, Li; Ma, Yi; Yang, Ping; Jiang, Dan; Liu, Aijun; Zhang, Lu; Li, Yan; Cheng, Yinchu; Dong, Fei; Zhao, Rongsheng; et al. (Frontiers in Pharmacology, 2022)
Objective: Continuous lenalidomide (LEN) therapy is important to achieve a therapeutic eﬀect in patients with multiple myeloma (MM) and non-Hodgkin lymphoma (NHL). However, despite dose adjustment according to kidney function, many patients discontinue LEN therapy because of hematological toxicity. To date, therapeutic drug monitoring (TDM) of LEN has not been performed in oncology, and no target concentration level has been yet deﬁned. The aim of this study was to evaluate the exposure-safety relationship of LEN and determine the target concentration for toxicity. Materials and methods: A prospective observational study was designed and implemented. Blood samples were collected at 0.5 hours (trough concentration, Cmin) before oral administration and one hour (C1h) thereafter on the day. Clinical data were gathered from patients’ medical records and laboratory reports. Outcome measures of hematological toxicity were deﬁned by the Common Terminology Criteria for Adverse Events. The concentration values were dichotomized by receiver operating characteristic (ROC) curve analysis, and the association between exposure and outcome was determined using the logistic regression model. Results: Out of the 61 patients enrolled in this study, 40 (65.57%) had MM, and 21 (34.43%) had NHL. Hematological toxicity was reported in 15 (24.59%) patients. The LEN Cmin showed remarkable differences (p=0.031) among patients with or without hematological toxicity, while no association between C1h values and toxicity was noted (p>0.05). By ROC analysis, a Cmin threshold of 10.95 ng/mL was associated with the best sensitivity/specificity for toxicity events (AUC=0.687; sensitivity=0.40; specificity=0.935). By multivariate logistic regression, an LEN Cmin below 10.95 ng/mL was associated with a markedly decreased risk of hematological toxicity (<10.95 ng/mL vs. >10.95 ng/mL: OR=0.023, 95% CI=0.002-0.269; p=0.003). Conclusions: We demonstrate that the LEN trough concentration correlates with hematological toxicity, and the Cmin threshold for hematological toxicity (10.95 ng/mL) is proposed. Altogether, LEN TDM appears to be a new approach to improve medication safety and achieve continuous treatment for patients with NHL or MM in routine clinical care.